Mothers’ Knowledge, Attitudes, And Behavior In Stunting Prevention Efforts: A Scoping Review - friescha friecillia martin; Sulistyaningsih Sulistyaningsih; Asri Hidayat (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Stunting is a global nutritional problem that has long-term effects on children’s physical growth and cognitive development. Mothers’ knowledge, attitudes, and behaviors play a crucial role in stunting prevention; however, prevention practices are also influenced by family support, access to health services, social conditions, and the intervention context. Previous studies have been limited in mapping the integrated relationship between mothers’ knowledge, attitudes, and behaviors in stunting prevention. This study aims to map the scientific evidence regarding mothers’ knowledge, attitudes, and behaviors in stunting prevention and to identify research gaps and directions for intervention development. Method: This study employed a scoping review using the Arksey and O’Malley approach and the PEOS framework. The study population consisted of mothers, with exposure defined as mothers’ knowledge, attitudes, and behaviors regarding stunting prevention, and the outcome as stunting prevention efforts. The study designs included quantitative, qualitative, and mixed-methods. Literature was obtained from PubMed, ScienceDirect, EBSCO, Wiley, Neliti, and Google Scholar, with criteria including primary articles, full text, in Indonesian or English, and published between 2015 and 2025. Article selection was conducted using Rayyan and reported via a PRISMA flowchart. Article quality was assessed using the Joanna Briggs Institute (JBI) for quantitative and qualitative studies, and the Mixed Methods Appraisal Tool (MMAT) for mixed-methods studies. Result: Of the 292 identified articles, 10 met the inclusion criteria. Findings indicate that while some mothers possess basic knowledge about stunting, their understanding of its causes and impacts remains limited. Mothers’ attitudes are influenced by education and employment status. Educational media interventions and culturally sensitive community-based education have proven effective in improving mothers’ knowledge, attitudes, and behaviors regarding stunting prevention. Conclusion: Mothers’ knowledge, attitudes, and behaviors play a crucial role in stunting prevention. Therefore, strengthening maternal education should be a policy priority in integrated efforts to improve long-term child health.